2015
DOI: 10.2196/mededu.4394
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Patients in a Behavioral Medicine Massive Open Online Course (MOOC): A Case-Based Analysis of Technical Capacity and User Navigation Pathways

Abstract: BackgroundMassive open online courses (MOOCs) have been criticized for focusing on presentation of short video clip lectures and asking theoretical multiple-choice questions. A potential way of vitalizing these educational activities in the health sciences is to introduce virtual patients. Experiences from such extensions in MOOCs have not previously been reported in the literature.ObjectiveThis study analyzes technical challenges and solutions for offering virtual patients in health-related MOOCs and describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Anecdotally, participants generally have a high level of satisfaction with Web-conferenced learning [ 12 , 14 - 16 ]. However, it should be emphasized that Web-conferenced learning is a generic term incorporating a wide range of online systems with varying levels of functionality ranging from simple synchronous communication tools to high-technology replication of clinical environments such as virtual patients [ 17 ]. A pilot study by our research team provided data showing that RO-CBL results in comparable learning outcomes when compared to face-to-face CBL.…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotally, participants generally have a high level of satisfaction with Web-conferenced learning [ 12 , 14 - 16 ]. However, it should be emphasized that Web-conferenced learning is a generic term incorporating a wide range of online systems with varying levels of functionality ranging from simple synchronous communication tools to high-technology replication of clinical environments such as virtual patients [ 17 ]. A pilot study by our research team provided data showing that RO-CBL results in comparable learning outcomes when compared to face-to-face CBL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of 'embedded videos' or 'online lessons / modules' are not interactive, despite author claims. Even in cases where articles in this study demonstrated an innovation in the MOOC space by, for example, including virtual patient cases in the traditional MOOC infrastructure, they still analysed outcomes using server logs and participant satisfaction surveys [39]. xMOOCs are arguably the least pedagogically sound variant if the outcome of interest is a qualitative change in teaching and learning behaviour, and they have been criticised for adopting a knowledge transmission mode of learning.…”
Section: Discussionmentioning
confidence: 99%
“…However one study [30] reported the participants were neutral in their assessment of satisfaction (Likert Scale score of 0.0 (95% CI − 1.1 to 1.2), and another [21] reported that only 56% of learners were satisfied with the quality of the course discussion forums. One study [39] provided strong agreement from participants for the helpfulness of a virtual patient experience. One study [21] included qualitative comments from participants, reporting that the course helped with self-discovery, and expanded their view of the world.…”
Section: Learner Experience (Attitudes Of Health Professionals Towardmentioning
confidence: 99%
See 1 more Smart Citation
“…MOOC delivery platforms allow educators to create and deliver interactive courses with videos, online resources, quizzes, virtual patients (Stathakarou , Zary, and Kononowicz 2014;Kononowicz et al, 2015 ) and an ability to interact with other students taking the course. This technology could allow students to learn at a time and place of their choosing, freeing valuable curricular time for hands on experiences.…”
Section: Introductionmentioning
confidence: 99%